Biochemical Processes of Lignocellulosic Biomass Conversion - Stanisław Ledakowicz (Energies, 2025)
After a brief characterisation of lignocellulosic biomass (LCB) in terms of its biochemical structure and the pretreatment techniques used to disrupt lignin structure and decrystallise and depolymerise cellulose, this review considers five main pathways for biochemical biomass conversion: starting with anaerobic digestion to convert various LCB feedstocks into bioproducts; considering the integration of biochemical and thermochemical processes, syngas fermentation, which has been recently developed for biofuel and chemical production, is reviewed; the production of 2G bioethanol and biobutanol from LCB waste is discussed; the literature on biohydrogen production by dark fermentation, photofermentation, and bioelectrochemical processes using microbial electrolysis cells as well as hybrid biological processes is reviewed. The conclusions and future prospects of integrating biochemical and thermochemical conversion processes of biomass are discussed and emphasised.